The Use of Coffee Husk as Napier Grass Substitution and Its Effect on Madura Cattle Performance - Asep Sudarman; G B Listiawan; L Khodijah (Jurnal Ilmu Ternak dan Veteriner, 2019)
This research aimed to evaluate the performance of fattened madura cattle fed on coffee husk as a source of fibre to substitute grasses. Twenty Madura steers aged approximately 1.5 to 2.0 years with initial weight of 165-190 kg were divided randomly into four different experimental diets, namely R0= 90% concentrates +0% coffee husk +10% napier grass, R1= 90 % concentrates +3.33% coffee husk +6.67% napier grass, R2 = 90% concentrate +10% 6.67% coffee husk +3.33% napier grass, R3 = 90% concentrates 90% + 10% coffee husk +0% napier grass. The feed was given at 3% body weight of dry mater. The cows were kept in individual pen for two months. Variables measured were dry mater intake, feed efficiency, average daily gain (ADG), digestibility of feed and income over feed cost. Data obtained were analyzed using analysis of variance based on randomized block design followed by Duncan’s multiple range test. Results showed that dry matter intake, ADG, feed efficiency and feed digestibility of cattle on each treatment of the feed were not significantly different (P > 0.05). Average of dry matter intake and daily gain for R0, R1, R2, and R3 were 6.01, 5.84, 5.73 and 5.62 kg/head/day and 0.88, 0.87, 0.84 and 0.93 kg/head/day respectively. While the average of feed efficiency and DM digestibility for R0, R1, R2, and R3 were 14.64, 14.89, 14.65 and 16.54 % and 84.82, 84.37, 83.47 and 83.30 %, respectively. It is concluded that the used of 10% coffee husk as a source of fibre for substitution of napier grass can be used without negative effect on madura’s cattle performances and tend to give higher values of IOFC on fattening program.